The study of the mutual effect between crisis strategies (Covid-19) and the organizational culture and organizational strategic orientation in private Jordanian universities - Mohannad Sami Tawaha (Cogent Business & Management, 2021)
The research aims at studying the mutual effect between the crisis strategies (Corona), organizational strategies and organizational culture in private Jordanian universities. (384) questionnaires were distributed by email to faculty members who perform administrative works, like the Head of Department and the Faculty Dean. However, only (250) were returned. The research used Partial Least Square Structural Equation Model (PLS-SEM) techniques. The results showed that the organizational strategic orientation was negatively affecting the crisis management strategies (Corona crisis). In addition, the result revealed a significant positive relationship between organizational strategic orientation and organizational culture. Moreover, organizational culture has a significant effect on the crisis management strategies (Corona crisis) in private universities. Furthermore, the results showed that organizational culture mediate the effect of organizational strategic orientation on crisis management strategies (Corona crisis).
Keywords: 650; Crisis management strategy; organizational strategy; organizational culture; PLS-SEM